Dexter time: the space, time, and matterings of school absence registration. Issue 2 (3rd March 2016) - Bodén, Linnea
Abstract : Working with a posthumanist approach, this article explores how the computer software Dexter, used for the registration of students' absences and presences, is part of the production of different practices of time, place, space, and matter in Swedish schools. The empirical material engaged with comes from two schools, and the students involved are in grades 7–9. The article creates knowledge on how the digital registration of students' presences, absences, or late arrivals is dependent upon material-discursive practices. The "bodily presences" of students are continually destabilized in relation to Dexter, showing that school absences and presences are (re)shaped depending on relations of spacetimematter.